2020
DOI: 10.1002/jac5.1210
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and evaluation of comprehensive medication management in telehealth practices

Abstract: The American College of Clinical Pharmacy (ACCP) endorses comprehensive medication management (CMM) as an essential element of team‐based care and advocates CMM inclusion in value‐based health care reform. Remote delivery of CMM through telehealth platforms is expanding and has the potential to become one of the most common clinical pharmacy services. Building on a previous ACCP publication, “Providing Comprehensive Medication Management in Telehealth,” the 2019 ACCP Clinical Practice Affairs A Committee provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Telepharmacy is primarily used in community, hospital, and ambulatory care settings to augment pharmacist coverage in rural and medically underserved areas. [20][21][22][23] Outcomes associated with telepharmacy services, particularly when combined with on-site pharmacy services, have been positive and include decreased medication errors, decreased order processing time, improved nursing satisfaction (because of the former), increased documentation of pharmacist interventions, and improved access to care. [21][22][23][24][25]…”
Section: Potential Benefitsmentioning
confidence: 99%
“…Telepharmacy is primarily used in community, hospital, and ambulatory care settings to augment pharmacist coverage in rural and medically underserved areas. [20][21][22][23] Outcomes associated with telepharmacy services, particularly when combined with on-site pharmacy services, have been positive and include decreased medication errors, decreased order processing time, improved nursing satisfaction (because of the former), increased documentation of pharmacist interventions, and improved access to care. [21][22][23][24][25]…”
Section: Potential Benefitsmentioning
confidence: 99%
“…The National Association of Boards of Pharmacy and the American Pharmacists Association both have definitions of “telehealth” or “telepharmacy” that address operations and regulatory considerations. 17,18 The American College of Clinical Pharmacy published guidance for clinical pharmacists providing CMM remotely via telehealth in alignment with the Standards for Practice of Clinical Pharmacists 19,20 …”
Section: Modifying Ambulatory Care Pharmacy Practicementioning
confidence: 99%
“…A comprehensive evaluation program is essential for the success and quality improvement of telehealth services 19 . A systematic review found traditional pharmacist telehealth programs in ambulatory care had an overall positive impact on outcomes related to laboratory value monitoring and achieving therapeutic goals 16 .…”
Section: Monitoring Clinical and Financial Outcomesmentioning
confidence: 99%
“…Access to telehealth resources will be essential to reach patients on home dialysis modalities to complete medication reconciliation and CMM services. Best practices for implementation of CMM via telehealth have been recently published and serve as an excellent resource for pharmacists starting these programs in nephrology practice 61 . The Kidney Care Choices models provide additional payments for a kidney disease education benefit, which can be provided by pharmacists as a qualified provider.…”
Section: Tools For Implementation Of Pharmacist‐based Care In Kidney mentioning
confidence: 99%
“… Note : The standards are adapted from successful Canadian models 61 and serve as a baseline for additional development by the newly formed Advancing American Kidney Health through Optimal Medication Management agenda. …”
Section: Next Stepsmentioning
confidence: 99%